Pengenalan Varietas Inbrida Padi Gogo (Inpago) Melalui Plot Percontohan di Nagori Sigodang Barat Kecamatan Panei Kabupaten Simalungun - Jonner Purba; Irawaty; Johnson A Marbun; Dameria Naibaho; Jhon Howad Siagian; Pebriadi Gultom (Jurnal Pengabdian Masyarakat Sapangambei Manoktok Hitei, 2022)
West Sigodang Nagori, Panei District, Simalungun Regency, is a nagori whose main livelihood is agriculture. Planting is done on mering land. The existing dry land is planted with food crops such as upland rice and corn, various vegetable crops, plantation crops including coffee, oranges, cocoa etc. Upland rice is a plant that is widely cultivated, the results are for their own needs. Upland rice planted are local varieties such as red sigambiri, white sigambiri, sipala, sironip and the others. Generally varieties have weaknesses such as deep age, low production, easy to fall and other weaknesses. The presence of a new upland rice variety called Inpago is a breakthrough that gives hope for increasing upland rice production. There are many varieties of Inpago that have been released to farmers for planting. From the results of several studies show that Inpago production is quite high. In addition, several Inpago varieties have adapted to land in the low to medium lands so that the distribution of their plantings has become more widespread. The pilot project (Demplot) held in West Sigodang Nagori is a way to introduce several Inpago varieties that have an agro-ecosystem that fits the nagori. In order to provide information about the growth and production of Inpago that is tested, several farmers are included in their cultivation and at harvest time, apart from farmers, local agricultural extension workers are also invited. Based on the yields, the farmers are interested in planting the Inpago Agritan variety and the seeds to be planted from the harvests of this pilot plot